2000
DOI: 10.1093/jac/46.5.657
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of perinatal HIV transmission during pregnancy

Abstract: Transmission of the human immunodeficiency virus (HIV) from mother to child can occur in utero, during labour or after delivery from breastfeeding. The majority of infants are infected during delivery. Maternal HIV-1 plasma viral load at delivery is the most important predictor of vertical transmission. For this reason, efforts to interrupt transmission have focused on the use of antiretroviral therapy. Zidovudine has been shown to reduce significantly vertical HIV transmission when used antepartum and intrapa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 64 publications
0
49
0
Order By: Relevance
“…1 H NMR spectra were recorded on a Bruker Avance III 400, a Bruker AV 500b, or a Bruker Avance III 600 (with cryoprobe) spectrometer, operating at 400, 500, and 600 MHz, respectively. 13 C NMR spectra were recorded on a Bruker ARX 400, a Bruker AV 500b, or a Bruker Avance III 600 (with cryoprobe) spectrometer, operating at 100.62, 125.77, and 150.92 MHz, respectively. Chemical shifts are reported in ppm downfield from tetramethylsilane, and coupling constants (J) are reported in Hz; the subscripts ortho, meta, and gem refer to ortho, meta, and geminal couplings, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 H NMR spectra were recorded on a Bruker Avance III 400, a Bruker AV 500b, or a Bruker Avance III 600 (with cryoprobe) spectrometer, operating at 400, 500, and 600 MHz, respectively. 13 C NMR spectra were recorded on a Bruker ARX 400, a Bruker AV 500b, or a Bruker Avance III 600 (with cryoprobe) spectrometer, operating at 100.62, 125.77, and 150.92 MHz, respectively. Chemical shifts are reported in ppm downfield from tetramethylsilane, and coupling constants (J) are reported in Hz; the subscripts ortho, meta, and gem refer to ortho, meta, and geminal couplings, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Excitation in 13 C was ensured by a 90°s haped sinc pulse (with one cycle and size shape 1000), covering a 4527.536 Hz bandwidth (centered at 21879.4 Hz); the total spectral width in F2 was 4 ppm (centered at 7 ppm). 13 C resonances are not discriminated whenever small sample quantities precluded the recording of one-dimensional 13 . The reaction mixture was incubated at 37°C for periods ranging from 2 to 7 days and subsequently purified by HPLC.…”
Section: Methodsmentioning
confidence: 99%
“…It is therefore reasonable to assume that the transmission of HBV to infants could be stopped by reducing the maternal serum viral load through lamivudine use during late pregnancy. [6] Several previous studies have shown the efficacy of using lamivudine in reducing vertical transmission of HBV. [7][8][9] However, evaluation is lacking on the effect of giving prophylactic lamivudine to mothers on long-term consequences in infants such as chronic hepatitis, compensated or decompensated liver cirrhosis and death from liver cirrhosis or liver cancer.…”
Section: Key Points For Decision Makersmentioning
confidence: 99%
“…Antiviral therapy during pregnancy and delivery, combined with elective caesarean section and replacement feeding, has been shown to reduce the incidence of HIV-1 transmission to less than 2% (15). Despite this success and although many factors that affect mother-to-child transmission are known, the exact mechanism remains unclear, and a thorough scientific base to further improve both therapeutic and preventive interventions is missing.…”
mentioning
confidence: 99%